A two-year field study of using a new material for remediation of cadmium contaminated paddy soil. (August 2020) - Zhao, Hanghang; Huang, Xunrong; Liu, Fuhao; Hu, Xiongfei; Zhao, Xin; Wang, Lu; Gao, Pengcheng; Ji, Puhui
Abstract: Cadmium (Cd) as a highly toxic heavy metal can cause seriously harmful to human health. Rice consumption is a major source of Cd intake by Chinese. Reduce the Cd accumulation by rice is the key for reducing Cd hazard. Therefore, fly ash (FA) was used as raw material in this study, after the process of simplifying hydrothermal synthesis the zeolite (ZE), which was named as low-temperature-alkali roasting, a new intermediate materials (IP) was got. And the three mentioned materials (FA, IP and ZE) were used for a two-year field experiment. The study demonstrated that, application of IP and ZE could promote rice growth, as well as increase soil pH, and improve available Si content. The rice production increased by 36.1% and 29.8% in 2017 by IP and ZE applied, enhanced 35.9% and 31.7% in 2018, respectively. Meanwhile, the bio-available Cd decreased by 26.9% and 26% in 2017, reduced by 22.9% and 28% in 2018, respectively. Generally, the passivators could promote the conversion of acid-exchangeable fraction Cd to reducible fraction Cd. It can be conclude that, IP and ZE have good remediation effect on contaminated soil, and alleviated effects on Cd accumulation by rice, even though no significant difference was detected between IP and ZE. The synthesis process of IP of is simpler than ZE. The impact of IP on contaminated soil needs further exploration. Graphical abstract: Image 1 Highlights: Fly ash can be modified as heavy metals passivators potentially. Synthesized materials enhanced the rice yield while decreased Cd accumulation. Cd concentrations of rice grains can be reduced lower than 0.2 mg kg −1 . The remediation effect of passivators persisted during two years experimental.